The Effectiveness of Red Guava Juice (Psidium guajava L.) and Crystal Guava Juice (Psidium guajava L. “Crystal”) on Physical Fitness of Female Adolescents with Anemia: EFEKTIFITAS JUS JAMBU BIJI MERAH (Psidium guajava L.) DAN JUS JAMBU KRISTAL (Psidium guajava L.“Chrystal”) TERHADAP KEBUGARAN JASMANI REMAJA PUTRI ANEMIA - Devi Ratna Mayasari; Yulia Sari; Ratih Puspita Febrinasari (Universitas Airlangga, 2023)
Anemia often occurs in female adolescents cause by iron deficiency. Adolescents are diagnosed anemia if the hemoglobin level is <12 g/dl. Someone who has anemia is prone to have low physical fitness. Consumption of foods that are high in iron and vitamin C such as guava juice can help improve physical fitness. The aim of this study was to analyze the effect of red guava juice and crystal guava juice consumption on physical fitness in female adolescents with anemia. The design of this study was a quasi-experimental with pre and post-test control group design with 36 subjects divided into 3 groups, namely control (iron tablets), P1 (iron tablets + red guava juice), P2 (iron tablets + crystal guava juice). Red guava juice and crystal guava juice given 200 ml per day for 30 days. The physical fitness test uses the Harvard Step Test method with a Physical Efficiency Index assessment. Physical fitness before and after control group had a difference of 1.84±15.86, the difference in P1 group was 17.20±20.35, and the difference in P2 group was of 19.69±15.58. Based on the results of statistical tests, it was found that there were differences in the three groups before and after the intervention p=0.031 (p<0.05). Giving red guava juice and crystal guava juice can be an alternative to improve physical fitness in female adolescents with anemia, but crystal guava juice is the most effective in increasing physical fitness in female adolescents with anemia.